Detection of Driver Drowsiness using Eye Blink Sensor - Kumari B.M, Kusuma; Sethi, Sampada; Kumar P, Ramakanth; Kumar, Nishant; Shankar, Atulit (International Journal of Engineering and Technology, 2018)
Accidents due to driver drowsiness can be prevented using eye blink sensors. The driver is supposed to wear the eye blink sensor frame throughout the course of driving and blink has to be for a couple of seconds to detect drowsiness. Any random changes in steering movement leads to reduction in wheel speed. The threshold of the vibration sensor can be varied and accordingly action can be taken. The outcome is that the vibrator attached to eye blink sensorâ€™s frame vibrates if the driver falls asleep and also the LCD displays the warning messages. The wheel is slowed or stopped depending on the condition. This is accompanied by the owner being notified through the GSM module, so the owner can retrieve the driverâ€™s location, photograph and police station list near to driverâ€™s location. This is how the driver can be alerted during drowsiness and the owner can be notified simultaneouslyÂ Â